2023
DOI: 10.1039/d2tb01179d
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid-based artificial nanocarriers for gene therapy

Abstract: Nucleic acid nanotechnology is a powerful tool in the fields of biosensing and nanomedicine owing to their highly editability, easy synthesis and modification. Artificial nucleic acid nanostructures become the emerging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 201 publications
0
4
0
Order By: Relevance
“…si-RNAs as antisense oligonucleotides (ASOs) can be used in oligonucleotide-based techniques to target overexpressed oncogenic lncRNAs, where they can bind specifically with lncRNAs, initiating their degradation via RNA-induced silencing complex (RISC) or RNase H (Kole et al, 2012;Raguraman et al, 2021;Scharner and Aznarez, 2021;Zhang and Zhang, 2023). Investigations on improved delivery methods, stability of the oligonucleotide, and their long-lasting effects on patients are underway (Glazier et al, 2020;Shadid et al, 2021;Zhu et al, 2023). Another therapeutic strategy to inhibit lncRNA is catalytic degradation using ribozymes.…”
Section: Treatment Strategies Using Lncrnasmentioning
confidence: 99%
“…si-RNAs as antisense oligonucleotides (ASOs) can be used in oligonucleotide-based techniques to target overexpressed oncogenic lncRNAs, where they can bind specifically with lncRNAs, initiating their degradation via RNA-induced silencing complex (RISC) or RNase H (Kole et al, 2012;Raguraman et al, 2021;Scharner and Aznarez, 2021;Zhang and Zhang, 2023). Investigations on improved delivery methods, stability of the oligonucleotide, and their long-lasting effects on patients are underway (Glazier et al, 2020;Shadid et al, 2021;Zhu et al, 2023). Another therapeutic strategy to inhibit lncRNA is catalytic degradation using ribozymes.…”
Section: Treatment Strategies Using Lncrnasmentioning
confidence: 99%
“…With the development of programmable RNA technology, there are some kinds of 2D and 3D frameworks of RNA, such as triangles, squares, pentagons, nanoprisms, tetrahedrons, and micelles, etc. 85,121–125 Stewart et al 126 designed a de novo double crossover (DX) RNA tile that can self-assemble and fold into lattices for siRNA delivery and demonstrated its remarkable stability in micron-scale. In breast cancer cells (MDA-MB-1/GFP), the material can achieve an excellent silencing efficiency for GFP, and showed silencing the similar efficiency for PLK1 in human prostate cell lines (PC1).…”
Section: Properties and Applications Of Nucleic Acid Nanomaterialsmentioning
confidence: 99%
“…This structure can self-assemble in PBS solution, without the need for divalent cations to maintain its stability. Their experiments further found that this structure had excellent serum and thermal stability, and demonstrated low toxicity and inammatory cytokines response.With the development of programmable RNA technology, there are some kinds of 2D and 3D frameworks of RNA, such as triangles, squares, pentagons, nanoprisms, tetrahedrons, and micelles, etc 85,[121][122][123][124][125]. Stewart et al126 designed a de novo double crossover (DX) RNA tile that can self-assemble and fold into…”
mentioning
confidence: 99%
“… 11 Furthermore, the development of efficient siRNA delivery systems, such as siRNA nanocarriers, in clinical trials has significantly advanced siRNA therapy. 12 This mini-review summarizes the latest advances and explores future prospects for understanding and treating psoriasis at the molecular level through RNAi technology. Specifically, it focuses on the key studies utilizing siRNA to target and silence key mediators of excessive proliferation in keratinocytes, inflammatory immune responses, cell signaling pathways, and the differentiation processes known to drive psoriasis formation.…”
Section: Introductionmentioning
confidence: 99%